73.6k views
1 vote
-(8x +4)-1=-7x- (x + 5)

1 Answer

7 votes

Answer: All real numbers; (−∞ ,∞) ; infinite solutions

Explanation:


-(8x +4)-1=-7x- (x + 5)

You want to distribute the (-) in (-(8x +4)) and (- (x + 5))


(-8x - 4) - 1 = -7x (-x - 5)

Combine like Terms on Both sides:


-8x - 5= -8x - 5\\\\\\

Add 5 to the right, and Add 8x to the left. (you want to cancel)


-8x - 5 = -8x -5\\+8x +5 \ \ +8x +5\\\\

You are left with:
0 = 0

If you are end with 0=0, that means both equations are equal regardless of the variables. Therefore the answer is all real numbers; (−∞ ,∞) ; infinite solutions. You could check by substituting any values, and getting the same answers on both sides.

User TheChrisKent
by
5.3k points